O Seesaw Inverso como mecanismo de geração de pequenas massas para os neutrinos - Sampieri, Adriano Rodrigues (2012)
For a long time it is known that neutrinos have mass and are also able to oscilate between their flavor states. However, the Standard Model only contain massless neutrinos, what lead us to believe that, among other known issues of the model, it is not the final theory. If we want to give an explanation to the neutrino masses we would have to extend the Standard Model in such a way to naturally accommodate these tiny masses. A great number of mechanisms appeared for such matters and the Canonical Seesaw Mechanism was highly accepted for its simplicity and beautifulness. Simple because it demands the addition of a minimal set of fields possible to obtain the neutrino mass at the order of sub-eV. Beautiful because it requires the breaking of lepton number at the scale of Great Unification Theories, bringging effects of high energy theories to low energy ones. Nevertheless, its beauty has a price. It will be impossible for the Canonical Seesaw Mechanism to be tested in recent and future experiments, hence new mechanisms emerged with the possibility of being probed by the experiments. We propose a mechanism based on the Inverse Seesaw Mechanism, which gives rise to the neutrino mass at sub-eV relying on a tiny leptonic breaking scale μ ∼ KeV. The Inverse Seesaw is not able to explain, in a natural way, the smallness of the μ parameter and it is here that our modifications emerge. With the introduction of new scalar fields and assuming a Z5⊗Z2 symmetry it is possible to dinamicaly explain the smallness of μ and also recover the Canonical Seesaw formula for the neutrino masses. Along with that, the right-handed neutrinos are able to be at the eletroweak scale, hence it is possible to test the model in actual experiments.